Implementasi Model Pembelajaran Cooperative Script Berbantuan Mind Mapping Dengan Model Pembelajaran Direct Instruction Terhadap Kemampuan Kreatifitas Mahasiswa Pada Mata Kuliah Microteaching - Junarti Junarti (JIPM (Jurnal Ilmiah Pendidikan Matematika), 2017)
this research is meant to:1) see the difference influence of Cooperative Script Model with the help of mind mapping with Direct Instructional teaching model to students’ creativity skill; 2) to prove the affectivity of Cooperative Script model implementation with the help of Mind Mapping in in improving Student’s creativity in applying basic teaching skill in Micro Teaching simulation activity; 3) to prove the implementation of Direct Instruction model in improving students’ creativity in applying basic teaching skill in micro teaching simulation. This research uses experimental method with two groups pre-test post-test. The result shows that: (1) the implementation of cooperative script model with the help of mind mapping is proven to be effective in improving student’s creativity in applying basic teaching skills in simulation activity can be seen from the experiment group where 11 skills (indicator formulation skill, apperception skill, opening skill, questioning skill, using variation skill, class management skill, discussion guidance skill, individual teaching skill, material mastery skill, class mastery skill and media usage skill) are showing the average score of more than 80, (2) the implementation of direct instruction model can improve student’s creativity in applying basic teaching skills where 6 basic skills (indicator formulation skill, giving apperception skill, lesson opening skill, questioning skill, class management skill and individual teaching skill) are able to achieve average scores of more than 80, and (3) the misconception done by students can be categorized as basic mathematical misconception which is caused by apperception mistake and understanding.Keywords: